2020
DOI: 10.1371/journal.pone.0238358
|View full text |Cite
|
Sign up to set email alerts
|

STK11 (LKB1) mutations in metastatic NSCLC: Prognostic value in the real world

Abstract: Background Mutations in STK11 (STK11m) and frequently co-occurring KRAS mutations (KRASm/ STK11m) are associated with poor survival in metastatic NSCLC (mNSCLC) immuno-oncology trials. There are limited data regarding the prognostic significance of these mutations in a real-world setting. Methods This retrospective cohort study analyzed de-identified electronic medical records from the Flatiron Clinico-Genomic database to identify patients with mNSCLC who had initiated firstline immunotherapy (IO; alone or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…No genetic alteration, including KRAS -mutant allele frequency or STK11 mutation status, was able to predict the anti-tumour activity, although baseline gene/protein expression of members of the HER family of receptor tyrosine kinase did exhibit a trend with the degree of anti-tumour response. A small molecule screen found that HER, SHP2, mTOR and CDK4/CDK6 inhibitors increased the response rate to MRTX849 in KRAS G12C mutant xenografts [ 28 ] STK11 co-mutations in KRAS mutant NSCLC have been associated with poor response to therapy [ 32 , 33 , 34 ]; the fact that mutation in this gene did not correlate with drug resistance in cell lines offers some hope for this generally refractory group.…”
Section: G12c Inhibitorsmentioning
confidence: 99%
“…No genetic alteration, including KRAS -mutant allele frequency or STK11 mutation status, was able to predict the anti-tumour activity, although baseline gene/protein expression of members of the HER family of receptor tyrosine kinase did exhibit a trend with the degree of anti-tumour response. A small molecule screen found that HER, SHP2, mTOR and CDK4/CDK6 inhibitors increased the response rate to MRTX849 in KRAS G12C mutant xenografts [ 28 ] STK11 co-mutations in KRAS mutant NSCLC have been associated with poor response to therapy [ 32 , 33 , 34 ]; the fact that mutation in this gene did not correlate with drug resistance in cell lines offers some hope for this generally refractory group.…”
Section: G12c Inhibitorsmentioning
confidence: 99%
“…A recent study reported a trend toward a reduced PFS in LUAD patients harboring STK11 mutations ( 20 ). Worse OS and PFS outcomes were also observed in NSCLC patients with STK11 mutations receiving immunotherapy or chemotherapy ( 30 ). Interestingly, Bange et al.…”
Section: Discussionmentioning
confidence: 99%
“…Serine/threonine kinase 11 ( STK11 ) is also one of the most frequently mutated genes in lung ADC [ 58 ]. Interestingly, mutations in this particular gene often co-occur with mutations of KRAS in NSCLCs [ 63 ]. Whether STK11 was presented as single or double mutations with KRAS , it was associated with worse overall survival (OS) and progression-free survival (PFS) in metastatic NSCLCs.…”
Section: Dysregulations and Aberrations Supporting Lung Carcinogenesismentioning
confidence: 99%